Division of labour and dissenting voting behaviour of MPs in a ‘working parliament’ - Mai, Philipp (European political science review, 2024)
In the literature on the determinants of party unity, one pathway has remained largely neglected: division of labour. Given their workload, members of parliament (MPs) are only thoroughly concerned with a subset of policies. We argue that this results in MPs casting fewer dissenting votes on matters within their area of specialization since they have had the opportunity to shape the party line there. Regression analyses using data for the German Bundestag support this hypothesis, including four important refinements: Not only the current but also past membership in the responsible committee reduces an MP’s defection probability. Additionally, this pattern is more pronounced for policy spokespersons and for less consequential, i.e., non-legislative votes as well as for issues less salient to the MP’s party. The results have implications for our understanding of MPs’ legislative behaviour, the functioning of parliaments as institutions and for the relationship between parties, MPs and voters.
Online veröffentlicht: 7. Juni 2023
Gesehen am 01.08.2024